Analysis of Corporate Bankruptcy Predictions PT. Gudang Garam Tbk using the Zmijewski Method (x-score) and Springate Method (S-Score) 2019-2023 - Marjohan, Masno; Latipah, Nunung; Ulfah, Siti Maryana; Gunawan, Rizkqi Aji (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Corporate bankruptcy prediction using the Zmijewski (X-Score) and Springate (S-Score) methods is a way for companies to anticipate potential bankruptcy. The aim is to help companies identify potential bankruptcy risks in a specific year or period and understand factors that might place them in a danger zone. This research aims to evaluate the financial condition of PT Gudang Garam Tbk using the Zmijewski (X-Score) and Springate (S-Score) methods from 2019 to 2023. This type of research is descriptive quantitative. The results show that the bankruptcy prediction analysis using both methods for PT Gudang Garam Tbk over the five years consistently indicates a healthy financial status.